Oxford International lower secondary English workbook 3 : grade 8 - Sullivan, Eve (Karachi : Oxford university press, 2023)
The Oxford International Lower Secondary English: Grade 8 Workbook by Eve Sullivan is a companion resource designed to reinforce and extend the learning covered in the Grade 8 Student Book. It provides additional practice and activities to help students consolidate their understanding of key English language skills, including reading, writing, speaking, listening, grammar, and vocabulary.
Keywords: English : Workbook grade 8